2004
DOI: 10.1186/1471-2407-4-68
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and immunoglobulin production by PWM-stimulated peripheral and tumor-infiltrating lymphocytes of undifferentiated nasopharyngeal carcinoma (NPC) patients

Abstract: Background: Undifferentiated Nasopharyngeal Carcinoma (NPC) patients show a characteristic pattern of antibody responses to the Epstein-Barr virus (EBV) which is regularly associated with this tumor. However, no EBV-specific cytotoxic activity is detectable by the standard chromiumrelease assay at both peripheral and intratumoral levels. The mechanisms underlying this discrepancy between the humoral and cellular immune responses in NPC are still unknown, but might be related to an imbalance in immunoregulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Compared to healthy individuals, the NPC patients exhibited elevated levels of IL-1b, IL-2 and IL-10, which is in accordance with previous findings in patients with NPC (34,35) and in tumor-bearing rodent models (36,37). Moreover, in our subgroup analysis, patients with depressive symptoms had specific overexpression of IL-1b while patients without depression did not, and the evaluated IL-1b was also found with significant positive association with depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to healthy individuals, the NPC patients exhibited elevated levels of IL-1b, IL-2 and IL-10, which is in accordance with previous findings in patients with NPC (34,35) and in tumor-bearing rodent models (36,37). Moreover, in our subgroup analysis, patients with depressive symptoms had specific overexpression of IL-1b while patients without depression did not, and the evaluated IL-1b was also found with significant positive association with depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have showed increased IL‐10 expression in epithelial NPC cells and IL‐10 serum level associations with undifferentiated NPC and clinical late stage (Yao et al ., 1997; Fujieda et al ., 1999; Budiani et al ., 2002), while others reported no detectable NPC cell expression of IL‐10 and no association with serum levels (Beck et al ., 2001; Tan et al ., 2006). Data on Tunisian patients indicate that tumour‐infiltrating lymphocytes of undifferentiated NPC produced more IL‐10 than their own peripheral blood lymphocytes, suggesting the possibility of an imbalance in immunoregulatory cytokines production in NPC (Fliss‐Jaber et al ., 2004). The literature concerning cytokine polymorphisms and NPC association is still too poor.…”
Section: Discussionmentioning
confidence: 99%
“…Also, no significant correlations were detected between CD8+ T cell density and gene expression of cytokines in noncancerous liver tissues. Fliss-Jaber et al [9] found that TIL of nasopharyngeal cancer patients produced significantly more IL-2 protein than peripheral blood lymphocytes. In our univariate and multivariate survival analysis, IL-2 mRNA expression in the tumor was recognized as one of the favorable prognostic factors of HCC patients.…”
Section: Discussionmentioning
confidence: 99%